An Erythrocyte Cytoskeleton-Binding Motif in Exported Plasmodium falciparum Proteins - Kilili, Geoffrey K. (American Society for Microbiology, 2011)

(untitled)
Binding of exported malaria parasite proteins to the host cell membrane and cytoskeleton contributes to the morphological, functional, and antigenic changes seen in Plasmodium falciparum-infected erythrocytes. One such exported protein that targets the erythrocyte cytoskeleton is the mature parasite-infected erythrocyte surface antigen (MESA), which interacts with the N-terminal 30-kDa domain of protein 4.1R via a 19-residue sequence. We report here that the MESA erythrocyte cytoskeleton-binding (MEC) domain is present in at least 13 other P. falciparum proteins predicted to be exported to the host cell. An alignment of the putative cytoskeleton-binding sequences revealed a conserved aspartic acid at the C terminus that was omitted from the originally reported binding domain. Mutagenesis experiments demonstrated that this aspartic acid was required for the optimal binding of MESA to inside-out vesicles (IOVs) prepared from erythrocytes. Using pulldown assays, we characterized the binding of fragments encoding the MEC domains from PFE0040c/MESA and six other proteins (PF10_0378, PFA0675w, PFB0925w, PFD0095c, PFF1510w, and PFI1790w) to IOVs. All seven proteins bound to IOVs, with MESA showing the strongest affinity in saturation binding experiments. We further examined the interaction of the MEC domain proteins with components of the erythrocyte cytoskeleton and showed that MESA, PF10_0378, and PFA0675w coprecipitated full-length 4.1R from lysates prepared from IOVs. These data demonstrated that the MEC motif is present and functional in at least six other P. falciparum proteins that are exported to the host cell cytoplasm.